Strategi Komunikasi Politik Dalam Membangun Opini Publik: Antara Narasi dan Realita - Siregar, Amran Pikal; Sazali, Hasan; Sayekti, Retno (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze political communication strategies in shaping public opinion, specifically how narratives constructed by political actors reflect or deviate from social reality in the digital era. The background of the problem includes a significant shift in political communication from one-way to a dynamic and participatory process through various digital platforms, where narratives are no longer limited to official speeches but evolve into visual, symbolic, and interactive content on social media. While this strategy is effective in building identity, emotional attachment, and influencing public perception of issues , problems arise when constructed narratives do not align with the reality faced by the public, which can lead to cognitive dissonance and a decline in public trust.The research employs a descriptive qualitative method, allowing for a comprehensive exploration of the meaning, context, and messages of political communication. Data collection involves document studies (social media posts, online news, campaign content, political speeches) and in-depth interviews with political communication practitioners, campaign teams, or media observers. Data are analyzed using qualitative content analysis to identify themes, symbols, language styles, and main messages , with source triangulation to ensure validity.The findings indicate that political actors strategically utilize emotional and identity-based narratives, such as justice, nationalism, and religion, as well as issue framing, to shape public opinion. The use of social media algorithms accelerates message dissemination and creates echo chambers, reinforcing polarization. Although effective in building psychological closeness and voter loyalty , the discrepancy between narrative and reality can potentially decrease public trust, trigger cognitive dissonance, a crisis of representation, and polarization. Therefore, healthy political communication must balance narrative with factual validity to strengthen credibility and foster democratic, inclusive, and educational communication.